Ruler with deep concern for people's welfare - News Straits, Times (New Straits Times, 2012)
KUALA LUMPUR: Tuanku Abdul Halim Mu'adzam Shah, who has created history by being elected twice as the Yang di-Pertuan Agong, is a nature loving monarch who has deep concern for the people's welfare.